Isotope discrimination by the stearoyl desaturase of Neurospora crassa - M Goodrich-Tanrikulu; A E Stafford; T A McKeon (Fungal Genetics Reports, 1999)
In wild type Neurospora crassa, we previously observed an unexpectedly low proportion of label in unsaturated fatty acids that should have been derived from deuterated palmitate (16:0). Interpretation of whether the position of deuteration could account for these results was inconclusive, because wild type had a low proportion of total fatty acids derived from the deuterated supplement. The N. crassa cel-1 strain is ideally suited for studies of fatty acid enrichment, because cel-1 must obtain its fatty acids exogenously. We supplemented cel-1 with 16:0's deuterated at different positions. With each of the labelled 16:0's, cel-1 desaturated the stearate (18:0) derived from the 16:0 more efficiently than wild type. However, when the 16:0 was deuterated at the site of future desaturation, we indeed observed effects on fatty acid composition and label distribution consistent with inhibition of the 18:0 desaturase.